Legal Analysis of Criminal Responsibility for Perpetrators of the Criminal Act of Extortion Committed Together (Case Study of Decision at Central Jakarta District Court Number 32/PID. B/2024/PN. JKT PST) - Safrul, Firman; Ariyana, Ade Riusma (KnE Social Sciences, 2025)
Crime is a form of behavior that is contrary to human morals (immoral), detrimental to society, asocial in nature, and in violation of laws. It is a social reality, and the problem of crime cannot be avoided and is always there, so it is natural that it causes unrest. One form of crime is extortion. Extortion is an act of selfishness that uses violence or threats against others to receive or achieve something. The main element of the crime of extortion, namely whether an act is included as a crime of extortion, is determined by the existence of intent or the will of the perpetrator to force another person by force, violence, or threats, to do or not do something. The approach method used is normative juridical, namely a library legal research conducted by examining library materials or secondary data only using deductive thinking methods. The writing specifications use descriptive analysis, and the sources and types of data used are primary and secondary data. The data were collected using secondary data collection methods. The problem is analyzed with the theory of criminal responsibility, and the theories of Pancasila justice and Islamic justice. Criminal liability for the perpetrators of extortion in Decision Number: 32/Pid.B/2024/PN JKT PST has fulfilled the value of criminal liability in accordance with the provisions of the actus because the defendant, namely ARF alias Jawa, has committed a prohibited act in accordance with that contained in Article 368 of the Criminal Code in conjunction with Article 55 Paragraph (1) Ke-1 of the Criminal Code, has been legally proven and guilty of committing the crime of theft, which is regulated and threatened with imprisonment of 1 year and 6 months each. The judge’s considerations in applying criminal provisions to the perpetrators in this case have been appropriate where the judge has considered both legal and non-legal considerations, facts in the trial, witness statements, existing evidence, and the judge’s conviction.